PERSEPSI MASYARAKAT TERHADAP PELAYANAN PENERBITAN E-KTP DI KANTOR KECAMATAN TAMPAN KOTA PEKANBARU - Winra A Pasaribu; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This essay was proposed to quality for a bachelor’s degree in Sociology. The title is,” Public Perception of E-KTP Service Tampan in Sub-District Office of Pekanbaru City”. The aim of this research to find out the public perception of E-KTP service in Tampan Sub-district Pekanbaru City and to find out the public characteristic who want to make E-KTP, and to find out how the public perception about the office clerk in Tampan Subdistrict of E-KTP service. The method of this research is perception and the idea is attendance and public. The location of this research in Tampan Sub-district, the population of this research every months was 245 people and the sample of this research was 20% or 49 people with random sampling. Data collection technique used observation, questionnaire and interview. The data are written in the table and are described quantitatively descriptively. The result of this research are in accordance with criteria interval values 3529-4704 categorized as good, and the conclusion of this research that the interval values of the calculation of all respondents answers includes good category, with the acquisition of 4104 divided by 5880 multiplied by 100% is 69,80%.Key Word : Perception, E-KTP Service